The Effect of Outward Foreign Direct Investment on International Labor Migration / ผลกระทบของการลงทุนโดยตรงในต่างประเทศต่อการเคลื่อนย้ายของแรงงานระหว่างประเทศ - / ชุติกา เกียรติเรืองไกร, Chutika Kiatruangkrai (Journal of Community Development Research (Humanities and Social Sciences); Vol 9 No 2 (2559): May-August 2016, 2016)
บทคัดย่อ งานวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาผลกระทบของการลงทุนโดยตรงในต่างประเทศ (Outward Foreign Direct Investment) ต่อการเคลื่อนย้ายของแรงงานระหว่างประเทศผู้ลงทุนและประเทศผู้รับทุนในทิศทางต่างๆ ที่มีการแบ่งกลุ่มประเทศตามระดับการพัฒนาทางเศรษฐกิจ โดยใช้แบบจำลองโน้มน้าว (Gravity Model) ในการประมาณค่าเพื่อประเมินผลกระทบดังกล่าวจากข้อมูลประเทศผู้ลงทุน 20 ประเทศ และประเทศผู้รับทุน 121 ประเทศ ระหว่างปี 1990-2010 (เป็นข้อมูลทุกๆ 5 ปี) ด้วยวิธี Pooled OLS ซึ่งผลการศึกษา พบว่า การลงทุนโดยตรงในต่างประเทศของทิศทางการลงทุนจากประเทศพัฒนาแล้วไปยังประเทศพัฒนาแล้ว (DC-DC) ไม่มีผลกระทบอย่างมีนัยสำคัญต่อการเคลื่อนย้ายของแรงงานขาเข้าซึ่งเคลื่อนย้ายมาจากประเทศผู้รับทุนมายังประเทศผู้ลงทุน ในขณะที่ทิศทางการลงทุนจากประเทศพัฒนาแล้วไปยังประเทศกำลังพัฒนา (DC-DI) มีนัยสำคัญในเชิงลบ นอกจากนี้ ผู้วิจัยยังทำการศึกษาถึงผลกระทบของปัจจัยทางเศรษฐกิจและมิใช่ทางเศรษฐกิจที่มีต่อการเคลื่อนย้ายของแรงงานขาเข้าในทิศทางดังกล่าว ซึ่งพบว่า ทิศทาง DC-DC จะขึ้นอยู่กับปัจจัยทางฝั่งของประเทศ ผู้ลงทุน ได้แก่ รายได้ต่อหัว ระดับของประชากร อัตราการว่างงาน และปัจจัยทางด้านการเมือง ส่วนทิศทาง DC-DI จะขึ้นอยู่กับปัจจัยด้านประชากรของทั้งประเทศผู้ลงทุนและประเทศผู้รับทุน และการเปิดการค้าระหว่างประเทศ สำหรับปัจจัยด้านเครือข่ายและปัจจัยด้านภูมิศาสตร์ พบว่า มีนัยสำคัญกับทั้งสองทิศทาง โดยทิศทาง DC-DI มีขนาดของผลกระทบมากกว่าทิศทาง DC-DC ในขณะที่ปัจจัยด้านวัฒนธรรม มีนัยสำคัญเพียงแค่ทิศทาง DC-DC เท่านั้น   คำสำคัญ : การลงทุนโดยตรงในต่างประเทศ  การเคลื่อนย้ายของแรงงาน  การพัฒนาทางเศรษฐกิจ  วิธี Pooled OLS   Abstract The objective of this paper is to analyze effects of outward foreign direct investment (OFDI) on international labor migration between home and host countries in the different direction of the flows which are classified by levels of economic development. By using gravity model to examine such effects with a sample including 20 home countries and 121 host countries during 1990-2010 (five-year intervals data), it is estimated by pooled OLS regression. This empirical result suggests that the effect of OFDI flows from developed countries to developed countries (DC-DC direction) on immigration, who moves from host to home countries, is not statistically significant as from developed countries to developing countries (DC-DI direction) is negatively significant. In addition, this paper also examines the economic and non-economic determinants of immigration in those directions and finds that DC-DC direction depends on home-country side factors such as per capita income, population level, unemployment rate and political factor. At the same time, DC-DI direction depends on demographic factors of both home and host countries and trade openness. Moreover, this result finds a significant role played by network and geographical factors in both directions, while cultural factors are statistically significant only in DC-DC direction.   Keywords: Outward Foreign Direct Investment, Migration, Economic Development, Pooled OLS
Keywords: การลงทุนโดยตรงในต่างประเทศ การเคลื่อนย้ายของแรงงาน การพัฒนาทางเศรษฐกิจ วิธี Pooled OLS Outward Foreign Direct Investment, Migration, Economic Development, Pooled OLS